(Pentafluorophenyl)diphenylphosphine as a dual-functional electrolyte additive for LiNi0.5Mn1.5O4 cathodes in high-voltage lithium-ion batteries. (10th March 2019) - Bolloju, Satish; Chiou, Chun-Yu; Vikramaditya, Talapunur; Lee, Jyh-Tsung
Abstract: (Pentafluorophenyl)diphenylphosphine (PFPDPP) is studied as an effective dual-functional additive for high-voltage LiNi0.5 Mn1.5 O4 (LNMO) cathodes. The additive can stabilize the LiPF6 salt and form a good cathode–electrolyte interphase (CEI). Hydrolysis of LiPF6 in the electrolyte is investigated by 19 F and 31 P nuclear magnetic resonance spectroscopy, which reveal that PFPDPP suppresses the decomposition of LiPF6 into LiF, PO3 F 2−, and PO2 F2 − . Cyclic voltammetry results reveal that PFPDPP is anodically decomposed at 3.5 V vs. Li/Li + prior to the oxidation of carbonate electrolytes to form a CEI film. The results of scanning electron microscopy, transmission electron microscopy, and AC impedance analyses show that PFPDPP forms a thin CEI film with low impedance. X-ray photoelectron spectroscopy results also confirm that the addition of PFPDPP suppresses the formation of LiF in the CEI film. Furthermore, the Li|1.0 M LiPF6 -EC/DEC (1:1, v/v)|LNMO cell with 0.2 wt% PFPDPP shows a retention capacity of 71% after 300 cycles at a charge–discharge rate of 2C between 3.0 and 5.0 V, whereas the cell without the additive shows a retention capacity of only 53.4% after 300 cycles. Furthermore, self-discharge of the battery is suppressed upon the addition of PFPDPP. Highlights: PFPDPP is investigated as an additive for high-voltage batteries. PFPDPP acts as a dual-functional additive that can stabilize both LiPF6 and CEI. The cell performance of the batteries is significantly improved with PFPDPP. Transition metal dissolution and self-discharge are suppressed by adding PFPDPP.